The predictive values of BOAH and No-apnea score for screening obstructive sleep apnea in rotating shift worker drivers. - Menezes Júnior, Luiz Antônio Alves de (2023)
Objective: To evaluate the BOAH (Body mass index, Observed apnea, Age, and Hypertension) and No-apnea score’s diagnostic values for detecting obstructive sleep apnea (OSA) risk in shift workers. Methods: Cross-sectional study with male rotating shift workers and drivers of heavy off-road machinery. The BOAH score is based on body mass index, witnessed apneas during sleep, age, and hypertension. The No-apnea score is based on neck circumference and age. Based on the apnea-hypopnea index (AHI), the severity of OSA was categorized as least mild OSA (AHI ≥5/h), moderate to severe OSA (AHI ≥15/h), and severe OSA (AHI ≥30/h). Sensitivity, specificity, positive predictive value, negative predictive value, and areas under the curve (AUC) were calculated. Results: Among 119 workers evaluated, 84.0% had AHI ≥5, 46.2% had AHI ≥15, and 14.3% had AHI ≥30. BOAH score with 2 points for AHI ≥5, the AUC was 0.679, and sensitivity and specificity were 41.0% and 94.7%, respectively. No-apnea score with 3 points AHI ≥5, the AUC was 0.692, and sensitivity and specificity were 70.0% and 68.4%, respectively. Furthermore, using at least one of the positive scores, the AUC was higher when compared to the single tests for AHI ≥5 (AUC = 0.727). And when both scores were positive, the AUC was higher for AHI ≥30 (AUC = 0.706). Conclusion: In rotating shift workers and drivers of heavy off-road machinery, BOAH, and No-apnea scores can be helpful tools in identifying individuals at risk for sleep apnea. In addition, matching the scores may increase the prediction of OSA.